Risk, monetary policy and asset prices in a global world - Geert Bekaert; Marie Hoerova; Nancy R. Xu (European Central Bank (ECB), 2023)
We study how monetary policy and risk shocks affect asset prices in the US, the euro area, and Japan, differentiating between "traditional" monetary policy and communication events, each decomposed into "pure" and information shocks. Communication shocks from the US spill over to risk in the euro area and vice versa, but traditional US shocks show no spillover effects to risk. Both monetary policy and communication shocks spill over to stocks, with euro area information spillovers being particularly strong. US spillovers are consistent with global CAPM intuition whereas euro area spillovers are larger. Importantly, we document a strong global component of risk shocks which is not driven by monetary policy.
Keywords: E44; E52; G12; G20; E32; 330; Risk; Monetary policy; International spillovers; Global Financial Cycle; Trilemma; Stock returns; Interest rate; Central Bank Communications